2019
DOI: 10.1039/c9py00461k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of irregularity from asymmetric random π-conjugated polymers on the photovoltaic performance of fullerene-free organic solar cells

Abstract: We synthesized a new random π-conjugated polymer (asy-PBDTPBT) and investigated the effect of its structural irregularity. The efficiency of non-fullerene OSCs was enhanced, showing the suppressed crystallinity and the smaller domain size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…[ 1–4 ] A great material library of new CPs have been established, which together with surface engineering of the device interfacial layers and optimization of device fabrication procedures, have led to significant improvements of device performances in many electronic applications such as organic thin‐film transistors (OFETs), organic solar cells (OSCs), and so on. [ 5–10 ] Among tremendous efforts to elevate their device performances, the material design of new CPs with novel molecular structures and ideal physicochemical properties serves as the cornerstone for the success of the organic electronic areas. [ 11–14 ] Specifically, the backbone structures of CPs, not only has a crucial effect on the intramolecular π‐orbital overlap and delocalization, but also play an important role for enhancing the inter‐(macro)molecular interactions via π–π stacking.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–4 ] A great material library of new CPs have been established, which together with surface engineering of the device interfacial layers and optimization of device fabrication procedures, have led to significant improvements of device performances in many electronic applications such as organic thin‐film transistors (OFETs), organic solar cells (OSCs), and so on. [ 5–10 ] Among tremendous efforts to elevate their device performances, the material design of new CPs with novel molecular structures and ideal physicochemical properties serves as the cornerstone for the success of the organic electronic areas. [ 11–14 ] Specifically, the backbone structures of CPs, not only has a crucial effect on the intramolecular π‐orbital overlap and delocalization, but also play an important role for enhancing the inter‐(macro)molecular interactions via π–π stacking.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that chlorination was an effective method to fine-tune conjugated polymer energy levels to improve device performance. Jin and co-workers 67 synthesized a novel random conjugated polymer asy-PBDTPBT (Fig. 5) and investigated the effects of random polymerization and the introduction of an asymmetric third component on its properties.…”
Section: Polymers Based On Symmetric Bdt and Asymmetric Unitsmentioning
confidence: 99%
“…Jin et al investigated the effect of irregularity ascribed to random 𝜋-conjugated random copolymers on the photovoltaic performance of NFA OSCs. [56] The group synthesized an asymmetric random copolymer, asy-PBDTPBT (herein P5), and used PB-DTP (herein P6) as the control polymer to prepare NFA OSCs. The best PCE value was obtained from the device based on P5:ITIC:Th active layer.…”
Section: Incorporated With Thiophenementioning
confidence: 99%